Implementation of Market Segmentation for Hijrah Scholar Takaful Insurance Products, Bank Muamalat, Sumenep Branch - Zaid Raya Argantara; Siti Maghfiroh Syamsul (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study analyzes the implementation of market segmentation on Hijrah Cendekia Takaful insurance products in Bank Muamalat Sumenep branch, supporting factors and inhibiting factors of hijrah cendekia takaful insurance products Bank Muamalat Sumenep Branch. Research methods using qualitative methods of Field (field research). Source data obtained from interview techniques, observation and documentation. The results of this study explain the segmentation of the insurance market Hijrah Cendekia Takaful Bank Muamalat Sumenep branch includes four things, namely Geographical segmentation in cities and villages in Sumenep regency, demographic segmentation from 20-65 years old, psychographic segmentation through motivation and expectations to be achieved by customers and behavioral segmentation of positive responses from customers regarding education in the future. The supporting factors of hijrah cendekia takaful Insurance are from the promotional strategies carried out by Bank Muamalat Sumenep branch so as to foster customer motivation who have the ability to economically use hijrah cendekia takaful insurance products for children's education in the future. Factors inhibiting scholar Takaful hijrah insurance is influenced by the lack of public understanding and limited economic conditions, the number of other institutions that offer the same product.